1999
DOI: 10.1046/j.1464-5491.1999.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral candidal carriage and infection in insulin‐treated diabetic patients

Abstract: The epidemiology of oral candidal carriage and infections in diabetic patients is complex and includes species which have not been previously reported in this group of patients. The development of oral candidosis in insulin-treated diabetes mellitus patients is not the result of a single entity, but rather, a combination of risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 20 publications
7
79
0
1
Order By: Relevance
“…Our data revealed that 20 (66.66%) of diabetic patients were found to carry Candida spp. in their oral cavity compared with the non-diabetic controls (26.66%), which was in accordance with the findings of the previous studies [19,20,21] . Although, among the Candida species, C. albicans has the Pink with a darker mauve center (2) C. kefyr…”
Section: Discussionsupporting
confidence: 92%
“…Our data revealed that 20 (66.66%) of diabetic patients were found to carry Candida spp. in their oral cavity compared with the non-diabetic controls (26.66%), which was in accordance with the findings of the previous studies [19,20,21] . Although, among the Candida species, C. albicans has the Pink with a darker mauve center (2) C. kefyr…”
Section: Discussionsupporting
confidence: 92%
“…These factors, as mentioned in the literature, include decreased salivary flow in diabetic patients because of altered salivary glands, 12 altered glucose levels in saliva that could facilitate adhesion of C. albicans to oral tissues, 31,30 uncontrolled blood glucose levels, 30 and use of dentures or poorly fitting dental appliances; 15,16,32,24 these factors would not act in isolation, but rather as a set of risk factors. 14,31,33 The palate is the most frequent site of these changes in both groups; it appears to be related more strongly with the presence of full upper dentures 13,24 as a possible predisposing factor for candidiasis. This infection was present in diabetic and non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Amato and Pecora (1983) analyzing 50 DM type II patients, without any lesion on the oral cavity, identified Candida albicans hyphae in the saliva of 25 (50%) patients. Willis et al (1999) demonstrated the presence of C. albicans in 77% of 414 DM patients using insulin, from which 40% did not present any clinical manifestation of candidiasis. Redinova and Zlobina (2002) performed an oral exam in 102 DM types I and II patients with, attesting the incidence of C. albicans in 78.4%, among these only 35% presented lesion on oral mucosa.…”
Section: Discussionmentioning
confidence: 96%